The Potency of Vitamin C as Prevention and Therapy Against COVID-19 Vitamin C Against COVID-19: A Systematic Review - Putri, Mirasari; Djajanagara, Raden Aliya T. M.; Syamsunarno , Mas Rizky A. A. (Writing Center IMERI FMUI, 2022)
COVID-19 affects more than 200 countries worldwide. This viral infection leads to systemic inflammation elevation, characterized by high pro-inflammatory cytokines and oxidative damage. Vitamin C (VC) functions as an antioxidant by protecting cells from oxidative damage and suppressing the cytokine storm's phenomenon. This review highlighted the possibility of VC for prevention and management in COVID-19. This review is a scoping review; literature searching was conducted using PubMed, Clinical Key, and Google Scholar until August 2020. The keywords used were COVID-19 and vitamin C. Sixteen articles were further analyzed. The reviewed studies consist of seven case reports, three case series, three cohort studies, and three bioinformatics analyses. Some studies highlight the improvement of the COVID-19 patient's condition after VC treatment combined with other therapies. In bioinformatics studies, all studies showed the therapeutic targets for VC in COVID-19 involved in inflammation and oxidative damage pathway. The mechanisms of VC against COVID-19 are associated with oxidative damage by acting as reactive oxygen species (ROS) scavengers or depressing the ROS production and cytokine storm pathways by suppressing pro-inflammatory cytokines and apoptotic process stimulation following the neutrophil activation.